2009
DOI: 10.1016/s1567-5688(09)71435-7
|View full text |Cite
|
Sign up to set email alerts
|

Abstract: P1427 EFFECTS OF SWEET POTATO (IPOMOEA BATATAS L.) LEAVES ON LDL OXIDATION AND ROS PRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Consumption of purple sweet potato leaves has been associated with decreased lipid peroxidation as well as reductions in LDL oxidation and reactive oxygen species production 61,68 . Chen et al 61 .…”
Section: Sweet Potato Leaves In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of purple sweet potato leaves has been associated with decreased lipid peroxidation as well as reductions in LDL oxidation and reactive oxygen species production 61,68 . Chen et al 61 .…”
Section: Sweet Potato Leaves In Health and Diseasementioning
confidence: 99%
“…Nagai et al. 68 found that sweet potato leaves exhibited considerable antioxidant inhibition of LDL oxidation both in vivo and in vitro. Sweet potato leaves were able to significantly prolong LDL lag time and were able to reduce indicators of lipid peroxidation and oxidative stress, namely plasma concentrations of thiobarbituric acid reactive substances.…”
Section: Sweet Potato Leaves In Health and Diseasementioning
confidence: 99%
“…Antioxidante Jeng et al (2015); Xi et al (2015); Chao et al (2014); Nagai et al (2009); Truong et al (2007); Huang et al (2004).…”
Section: Propriedades Farmacognósticas Artigosmentioning
confidence: 99%
“…Research has demonstrated reductions in CVD risk following consumption of these green leafy vegetables, both in vivo and in vitro [18-22]. Although epidemiological evidence has affirmed the association between GLV consumption and reductions in disease risk, there is limited research examining the effects of diets containing collard greens (CG), purslane (PL) and sweet potato greens (SPG) on cardiovascular disease risk, namely liver fatty acid profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Collard greens ( Brassica oleracea ), a traditional GLV consumed mainly in the southern region of the United States, in addition to purslane ( Portulaca oleracea ) and sweet potato greens ( Ipomoea batatas L.), novel GLVs to the typical American diet, may prove beneficial in reducing the risks associated with CVD development and progression [ 13 - 17 ]. Research has demonstrated reductions in CVD risk following consumption of these green leafy vegetables, both in vivo and in vitro [ 18 - 22 ]. Although epidemiological evidence has affirmed the association between GLV consumption and reductions in disease risk, there is limited research examining the effects of diets containing collard greens (CG), purslane (PL) and sweet potato greens (SPG) on cardiovascular disease risk, namely liver fatty acid profiles.…”
Section: Introductionmentioning
confidence: 99%